Perception of basic emotions in clinical improvisations : an experimental study - Kontoniemi, Sanna-Mari (2016)
Recently the Finnish music therapy research has focused on therapy of clients with depression. In music psychology the global interest in felt and perceived emotions in music has been a clear trend for two to three decades. This experimental study shares the interests of both fields by examining perceived emotions in improvised music from music therapy sessions.